Reductive dechlorination of gamma-hexachlorocyclohexane using Fe-Pd bimetallic nanoparticles - Nagpal, Varima; Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Journal of Hazardous Materials, 2010)
Nanoscale Fe-Pd bimetallic particles were synthesized and used for degradation of lindane (gamma-hexachlorocyclohexane) in aqueous solution. Batch studies showed that 5 mg/Lof lindane was completely dechlorinated within 5 min at a catalyst loading of 0.5 g/L and the degradation process followed first-order kinetics. GC-MS analysis in corroboration with GC-ECD results showed the presence of cyclohexane as the final degradation product. The proposed mechanism for the reductive dechlorination of lindane involves Fe corrosion-induced hydrogen atom transfer from the Pd Surface. The enhanced degradation efficiency of Fe-Pd nanoparticles is attributed to: (1) high specific surface area of the nanoscale metal particles (60 m(2)/g), manyfold greater that of commercial grade micro- or milli-scale iron particles (similar to 1.6 m(2)/g); and, (2) increased catalytic reactivity due to the presence of I'd on the Surface. Recycling and column studies showed that these nanoparticles exhibit efficient and sustained catalytic activity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bimetallic; Cyclohexane; Degradation; kinetics; Lindane; Nanoparticles

Au based Ni and Co bimetallic core shell nanocatalysts for room temperature selective decomposition of hydrous hydrazine to hydrogen - Jain, P.; Anila, K. A.; Vinod, C. P. (ChemistrySelect, 2019)
Nickel and Cobalt bimetallic catalysts with Au as core metal has been synthesized and demonstrated for hydrazine decomposition reaction for producing hydrogen. Gold-cobalt and gold nickel bimetallic system belonging to the class of strained structures with high lattice mismatch of approximately 14% are demonstrated for synergistic effects atypical of monometallic counterparts for the selective decomposition of hydrous hydrazine to H-2 with N-2 as the other product at room temperature.
Keywords: (HDR); Au@Co.; Au@Ni.; Bimetallic; catalyst.; core; decomposition; Hydrazine; nanoparticles.; reaction; shell

Bimetallic ZnFe2O4 nanosheets prepared via electrodeposition as binder-free high-performance supercapacitor electrodes - Joshi, Bhavana; Samuel, Edmund; Park, Chanwoo; Kim, Yongil; Lee, Hae-Seok; Yoon, Sam S. (Applied Surface Science, 2021)
Binder-free bimetallic ZnFe2O4 nanosheets were fabricated using one-step electrodeposition, which facilitated excellent electrical contact between the ZnFe2O4 nanosheets and the nickel substrate. The resultant numerous ZnFe2O4 nanosheets with their cubic spinel structures promote interfacial activity to enhance the electrochemical and Faradaic redox reactions. The metallic Zn and Fe from the cubic spinel structure of ZnFe2O4 attract electrolytic ions and increase the energy-storage capability, thus yielding a specific capacitance of 1093 F.g(-1) at a current rate of 1 A.g(-1). Different samples were prepared by varying the amount of metal salts in the electrodeposition solution while maintaining a constant ZnNt:FeSO4 concentration ratio of 1:2 for all cases. The optimal electrode composition, which yielded an energy density of 54 Wh.kg(-1) and a capacitance retention of 93.5% at N = 5000 charge-discharge cycles, was identified.
Keywords: Bimetallic; Electrodeposition; Energy storage device; supercapacitor; ZnFe2O4 nanosheet